2022
DOI: 10.3390/foods11233885
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Peptidomics Analysis of Milk Fermented by Lactobacillus helveticus

Abstract: Lactobacillus helveticus is one of the commonly used starter cultures for manufacturing various fermented dairy products. However, only a few studies have explored the cleavage region preference of L. helveticus with different cell envelope proteinase (CEP) genes. In the present study, we profiled the peptide composition of milk samples fermented by three different L. helveticus strains by means of peptidomics to illustrate their different proteolysis patterns. The result revealed that the differences in pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Therefore, it is speculated that calcium ions remained in a binding state to macromolecules during in vitro digestion. The pattern of sustained release of calcium and high solubility of LHWCC during simulated intestinal digestion might be partially attributed to the presence of peptides in LHW [ 15 , 32 ] as supported by the upregulation of PepT1 in vivo. Anyway, previous research found that during the simulated in vitro digestion process of the intestine, the solubility of CaCO 3 was between 60 and 80% [ 9 ], whereas that of Ca 3 (PO 4 ) 2 was below 20%, with significant differences in solubility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is speculated that calcium ions remained in a binding state to macromolecules during in vitro digestion. The pattern of sustained release of calcium and high solubility of LHWCC during simulated intestinal digestion might be partially attributed to the presence of peptides in LHW [ 15 , 32 ] as supported by the upregulation of PepT1 in vivo. Anyway, previous research found that during the simulated in vitro digestion process of the intestine, the solubility of CaCO 3 was between 60 and 80% [ 9 ], whereas that of Ca 3 (PO 4 ) 2 was below 20%, with significant differences in solubility.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus helveticus is one of the commonly used lactic acid bacteria in the production of fermented dairy products such as yogurt and cheese [ 11 ]. It has a strong protein hydrolytic ability, which endows its fermented dairy products with rich and diverse bioactive peptide profiles with functions in the regulation of blood pressure [ 12 ], the immune system [ 13 ], cognition [ 14 ], et al L. helveticus CCFM1263 has been shown to be highly efficient in casein hydrolysis and the generation of bioactive peptides [ 15 ]. The dairy protein hydrolysates of L. helveticus CCFM1263 would be a desirable agent for the development of functional calcium chelates.…”
Section: Introductionmentioning
confidence: 99%
“…Low purity β-casein as a bioactive peptide feedstock and a natural carrier for bioactive compounds β-Casein has excellent digestive properties. During digestion, β-casein is degraded into a variety of biologically active peptides (Gao et al, 2022;Kuellenberg de Gaudry et al, 2022;Schmelzer et al, 2007). These peptides have the ability to regulate digestive metabolism, balance hormones, and enhance body immunity (Asledottir et al, 2017;Deglaire et al, 2019;Naika et al, 2018).…”
Section: 12mentioning
confidence: 99%
“…It has the ability to metabolize lactose into exopolysaccharides, vitamins, and several flavor compounds [ 5 ]. Lactobacillus helveticus is a widely used starter culture in the production of yogurt, Italian cheeses, and Swiss cheeses, exhibiting probiotic properties such as gastrointestinal survival, epithelial cell adhesion, and pathogen antagonism [ 6 , 7 ]. It also acts as an effective inhibitor of angiotensin-converting enzyme, providing potential benefits for managing hypertension [ 8 ].…”
Section: Introductionmentioning
confidence: 99%